2017
DOI: 10.1039/c7ra02916k
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis and immobilization of a Cu(ii)–pyridyl complex on silica microspheres as a novel Fenton-like catalyst for RhB degradation at near-neutral pH

Abstract: A Cu(ii)–pyridyl complex was in situ synthesized and immobilized onto silica microspheres as a highly effective Fenton-like catalyst at near-neutral pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 57 publications
1
27
1
Order By: Relevance
“…We then studied the possible influence of the quantity of hydrogen peroxide in the oxidation capacity of the copper-based material, observing that, in all cases, at higher quantities of hydrogen peroxide in the mixture (more than 0.5 mL hydrogen peroxide in the reaction mixture) the oxidation capacity (TON) is higher at 6 h than at 24 h (See Table S1 of supplementary material). This behavior may be explained by the possibility of Fenton-like degradation processes which may be present at high quantities of hydrogen peroxide as observed previously in several other studies [68,69]. The Fenton-like degradation processes may lead to decomposition of benzaldehyde and/or benzyl benzoate, reducing the apparent total TON of the oxidation reactions.…”
Section: Resultssupporting
confidence: 62%
“…We then studied the possible influence of the quantity of hydrogen peroxide in the oxidation capacity of the copper-based material, observing that, in all cases, at higher quantities of hydrogen peroxide in the mixture (more than 0.5 mL hydrogen peroxide in the reaction mixture) the oxidation capacity (TON) is higher at 6 h than at 24 h (See Table S1 of supplementary material). This behavior may be explained by the possibility of Fenton-like degradation processes which may be present at high quantities of hydrogen peroxide as observed previously in several other studies [68,69]. The Fenton-like degradation processes may lead to decomposition of benzaldehyde and/or benzyl benzoate, reducing the apparent total TON of the oxidation reactions.…”
Section: Resultssupporting
confidence: 62%
“…where A is the pre-exponential factor, E a is the activation energy (kJ mol −1 ), R is the perfect gas constant (8.3 J•mol −1 K −1 ) and T is the absolute temperature (K) and k is the reaction constant. The calculated E a was approximately 35.9 kJ mol −1 , which was smaller than the values reported in the literature [23].…”
Section: Effect Of Temperaturecontrasting
confidence: 71%
“…For example, Li et al reported on rice-hull based silica supported iron catalyst for the efficient removal of RhB with the activation energy of about 82.35 kJ mol −1 [22]. In another study, Li et al reported a Cu (II)-pyridyl complex on silica microspheres for the degradation of RhB at neutral pH with an activation energy of about 38.6 kJ mol −1 [23]. Furthermore, the reusability of the catalyst was also studied.…”
Section: Introductionmentioning
confidence: 99%
“…11 Several hybrid composites have recently been fabricated by immobilizing copper on the organic, inorganic or hybrid compounds and then utilized as efficient catalytic or antibacterial systems. [12][13][14][15][16] MCRs are one-pot methods in which simple initial materials incorporated into the direct manufacture of complex structures. 17,18 Atomic economy, high efficiency, convergence, high bond-forming index are such outstanding features of MCRs.…”
Section: Introductionmentioning
confidence: 99%